2004
DOI: 10.1073/pnas.0406499101
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis identifies that 14-3-3ζ interacts with β-catenin and facilitates its activation by Akt

Abstract: ␤-Catenin is a central effector of Wnt signaling in embryonic and stem cell development and in tumorigenesis. Here, through a mass spectrometric analysis of a ␤-catenin protein complex, we identified 12 proteins as putative ␤-catenin interactors. We show that one of them, 14-3-3 , enhances ␤-catenin-dependent transcription by maintaining a high level of ␤-catenin protein in the cytoplasm. More importantly, 14-3-3 facilitates activation of ␤-catenin by the survival kinase Akt and colocalizes with activated Akt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
144
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(158 citation statements)
references
References 37 publications
10
144
4
Order By: Relevance
“…Endocytosis is regulated by phosphorylation (Shikano et al, 2006). 14-3-3 binds to specific phosphorylated (pSerine/pThreonine) motifs in its protein targets and occupancy protects the site from phosphatases (Petosa et al, 1998;Tian et al, 2004). It remains to be determined whether 14-3-3 may regulate α3*nAChR surface expression by this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Endocytosis is regulated by phosphorylation (Shikano et al, 2006). 14-3-3 binds to specific phosphorylated (pSerine/pThreonine) motifs in its protein targets and occupancy protects the site from phosphatases (Petosa et al, 1998;Tian et al, 2004). It remains to be determined whether 14-3-3 may regulate α3*nAChR surface expression by this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…4). The phosphorylated forms of PTEN and Akt, along with the adaptor protein 14-3-3ζ, have been found in ISCs 9,19 . Extending these findings, we found that cells in the ISC position, as well as a limited number of progenitor cells higher in the crypt, were highly positive for phosphorylated PTEN (p-PTEN), p-Akt, p-GSK3β, 14-3-3-ζ and Musashi ( Fig.…”
Section: Pten-akt Pathway Linked To Isc/p Cell Number and Behaviormentioning
confidence: 99%
“…We have proposed that Akt coordinates with Wnt signaling and assists in the activation of β-catenin in ISCs 9 , either through phosphorylation of GSK3β (ref. 37) or by phosphorylation of β-catenin itself 19 .…”
Section: Akt Phosphorylates the C Terminus Of β-Catenin At Ser552mentioning
confidence: 99%
See 2 more Smart Citations